Preliminary study on the time-correlation changes in brain neurotransmitters of mice exposed to mushroom toxin ibotenic acid - Dai, Ruanxian; Duan, Zhantao; Han, Bin; Chen, Guobing; Wang, Fuping; Shi, Zhuange; Zhou, Xian; Song, Haifei; Ma, Li; Meng, Qiang (Frontiers in Neuroscience, 2025)
BackgroundMushroom poisoning represents a significant food safety issue globally, particularly neurotoxic mushroom poisoning, which raises considerable concern due to its potential to induce central nervous system symptoms. Ibotenic acid is identified as the primary neurotoxin associated with this form of poisoning; however, the underlying mechanisms of its neurotoxicity remain poorly understood.ObjectiveThis study aims to systematically evaluate the effects of ibotenic acid exposure across three consecutive key time points, from intoxication to recovery, on neurotransmitters related to the GABA/Glutamic-Acid, dopaminergic, serotonergic, and cholinergic systems in five brain regions: the cerebral cortex, hippocampus, striatum, brain stem, and cerebellum.MethodsThrough behavioral tests, we assessed the effects of ibotenic acid exposure on voluntary activities and learning and memory functions in mice. Additionally, we analyzed the changes in neurotransmitter concentrations across different brain regions using targeted metabolomics.ResultsBehavioral results indicated that the total movement distance and speed in the open field test were significantly reduced, while the resting time was prolonged in the ibotenic acid-exposed group (P < 0.0001). The results of targeted metabolomics demonstrated that, compared to the control group, levels of glutamic acid in the hippocampus and brain stem significantly decreased after 4 h of ibotenic acid exposure (P < 0.05, P < 0.001). Additionally, epinephrine levels in the cerebral cortex decreased at 20 min (P < 0.05), while tyrosine levels in the brain stem and cerebellum decreased after 4 h (P < 0.05). In the brain stem region, the tryptophan levels in each exposure group decreased significantly compared with the 4-h exposure group (P < 0.01), and brain stem choline levels significantly decreased (P < 0.05). Conversely, homovanillic acid levels in the brain stem increased (P < 0.01).ConclusionPreliminary studies have demonstrated that acute exposure to ibotenic acid inhibits motor activity but does not significantly affect learning and memory in mice. Exposure to ibotenic acid induces alterations in GABA/Glutamic-Acid, dopaminergic, serotonergic, and neurotransmitters associated with the cholinergic system in the brains of mice, with the most pronounced changes occurring in the brain stem region, exhibiting time-dependent and region-specific effects. This study offers new insights into the neurotoxic mechanisms of ibotenic acid.